2021
DOI: 10.1084/jem.20201206
|View full text |Cite
|
Sign up to set email alerts
|

Meteorin-like/Meteorin-β protects heart against cardiac dysfunction

Abstract: Meteorin-like/Meteorin-β (Metrnl/Metrnβ) is a secreted protein produced by skeletal muscle and adipose tissue that exerts metabolic actions that improve glucose metabolism. The role of Metrnβ in cardiac disease is completely unknown. Here, we show that Metrnβ-null mice exhibit asymmetrical cardiac hypertrophy, fibrosis, and enhanced signs of cardiac dysfunction in response to isoproterenol-induced cardiac hypertrophy and aging. Conversely, adeno-associated virus–mediated specific overexpression of Metrnβ in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 48 publications
1
31
1
Order By: Relevance
“…A very recent study revealed that mice lacking Metrnl are prone to develop cardiac hypertrophy and Metrnl can act directly in cardiomyocytes to protect against hypertrophic processes in mice. 11 We and others previously reported that decreased serum Metrnl levels are associated with the presence and severity of coronary artery disease in humans. 12,13 However, the relationship between serum Metrnl and CHF in the elderly remains to be further elucidated.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…A very recent study revealed that mice lacking Metrnl are prone to develop cardiac hypertrophy and Metrnl can act directly in cardiomyocytes to protect against hypertrophic processes in mice. 11 We and others previously reported that decreased serum Metrnl levels are associated with the presence and severity of coronary artery disease in humans. 12,13 However, the relationship between serum Metrnl and CHF in the elderly remains to be further elucidated.…”
Section: Introductionmentioning
confidence: 85%
“…The exact mechanism for linking Metrnl to the pathogenesis and progression of CHF is yet to be clarified. Besides muscle and adipose tissue, heart is also a source of expression and release of Metrnl 10,11 . Results from experimental studies have shown that Metrnl can attenuate doxorubicin‐induced cardiotoxicity via activating cyclic AMP/protein kinase A/Sirtuin1 pathway and reduce ischemia/reperfusion injury‐induced cardiomyocyte apoptosis via activation of AMP‐activated protein kinase/p21 activated kinase 2 signalling, 9,10 indicating that Metrnl may play important roles in cardiac repair in response to various types of injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to infer that subfatin might be a predictor of cardiac systolic dysfunction in STEMI patients. Rupérez et al [73] proposed that the specific overexpression of subfatin in the heart prevents the development of cardiac remodeling. In addition, subfatin was a novel biomarker of heart failure and had an independent prognostic value.…”
Section: Subfatin and Cadmentioning
confidence: 99%
“…METRNL is produced upon stimulation by exercise and promotes adipose tissue browning via alternative macrophage induction at adipose depots [ 22 ]. Further research revealed that METRNL plays a protective role in cardiac dysfunction and lipid-induced muscle insulin resistance by ameliorating inflammation [ 23 , 24 ]. In the present study, we used HFD-induced obese mice and isolated bone marrow-derived macrophages (BMDMs) to examine how exercise and METRNL regulate the activation of NLRP3 inflammasome.…”
Section: Introductionmentioning
confidence: 99%